The Effect of ESG Score on Stock Return: Do Financial Performance and Market Performance Moderate? - Nurnaningsih, Dwi; Handajani, Lilik (E-Jurnal Akuntansi; Vol 35 No 6 (2025), 2025)
This study is intended to examine the effect of ESG Score on Stock Return with Financial and Market Performance as moderating variables. The research method is associative quantitative, with the object of research on companies listed in ESG Sector Leaders IDX KEHATI Index from 2019 to 2023. Based on purposive sampling technique, there were 18 companies with the number of observations narrowed because there were a number of outlier data, resulting in 44 observations. Panel data were analyzed with Moderated Regression Analysis (MRA) using the Eviews 12 program. The results of empirical testing show that ESG scores have a significant and positive effect on stock returns. And financial performance proxied through ROA strengthens the correlation of ESG scores and stock returns, while the ROE proxy is unable to moderate the relationship between the two variables. On the other hand, market performance (TQ) weakens the correlation between ESG scores and stock returns. Thus, ESG scores can be an indicator of sustainable investment considerations with high potential returns.  Keywords: ESG Score; Stock Return; Sustainability; Return on Assets; Tobin’s Q